1963
DOI: 10.1001/jama.1963.03710020029006
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Surgical Approach to the Management of Axillary Hyperidrosis

Abstract: (Fig 1, top). The number of active eccrine sweat glands in the central axilla approximates 175/sq cm, slightly more than in the skin of the forearm.1 Fewer glands are found in the poles of the axilla, however, where there is an associated thinning of the subcutis (Fig 2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

1977
1977
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(21 citation statements)
references
References 1 publication
0
20
0
1
Order By: Relevance
“…However, other authors 4,11 challenge this theory and are convinced that eccrine glands can be found also at the border of the dermis to the subcutaneous tissue. Still other authors 6,15,17,18 claim that both types of glands are found conjointly either in the subcutaneous tissue or in the dermis. Thus, the controversy on the localization of the different types of sweat glands in the axilla remains unresolved and leads to uncertainty for surgeons regarding which type of surgery will lead to the maximum of success.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, other authors 4,11 challenge this theory and are convinced that eccrine glands can be found also at the border of the dermis to the subcutaneous tissue. Still other authors 6,15,17,18 claim that both types of glands are found conjointly either in the subcutaneous tissue or in the dermis. Thus, the controversy on the localization of the different types of sweat glands in the axilla remains unresolved and leads to uncertainty for surgeons regarding which type of surgery will lead to the maximum of success.…”
mentioning
confidence: 98%
“…10 Type I removes (i.e., excises, curettes, suctions, or vaporizes) only the subcutaneous tissue and spares the skin [11][12][13] ; type II removes subcutaneous tissue and skin en bloc, mostly in the dome of the axilla 8,14 ; and type III is a combination of type I and II, with removal of subcutaneous tissue and skin en bloc centrally and removing only subcutaneous tissue in the adjacent areas. 4,10,15 Many of these surgical methods are based on the long-standing theory that eccrine glands are localized in the dermis and apocrine glands are localized in the subcutaneous tissue. 10,16 If this theory were true, the surgical method of choice was type I for bromhidrosis and type II or type III for hyperhidrosis.…”
mentioning
confidence: 99%
“…Excision Since a report in 1963 recommending elliptical excision of the axillary vault, 48 various excisional techniques have been described to remove or disrupt the sweat production apparatus within the axilla. 49,50 Success rates have ranged from 50 to 90%, and complications may include infection, bleeding, delayed healing, flap necrosis, significant scarring, or scar contracture.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Invasivere Operationen mit großen Schnitten zur Entfernung des subkutanen Gewebes [55] oder die kombinierte En-bloc-Exzision von Haut und subkutanem Gewebe in unterschiedlichen Ausmaßen [4,27,28] wurden durch schonendere Eingriffe mit minimalen Schnitten und anschließender subkorealer Kürettage [29,42,48] oder Saugkü-rettage [13] weitgehend verdrängt. Hierbei werden in zumeist nur Tumeszenzanästhe-sie kleine Schnitte wahlweise an einem oder beiden Polen der Achsel gesetzt und dann entweder mit einer scharfen Kürette oder mit einer Saugkürette das betroffene Areal quasi unterhöhlt (⊡ Abb.…”
Section: Kürettage Bzw Saugkürettageunclassified